The pattern of visual impairment in the spectrum of hypoxic ischemic encephalopathy - Swati Phuljhele; Niranjana Balasubramaniam; Gunjan Saluja; Rohit Saxena; Pradeep Sharma; Pavan Kumar; Sanjay Kusiyait; Sheffali Gulati (Indian Journal of Ophthalmology)
Purpose: This study aimed to evaluate the relationship between visual impairment, social maturity, and clinical severity of hypoxic-ischemic encephalopathy (HIE) in the Indian population. Methods: An observational study was conducted in children with HIE sequelae aged between 6 months and 5 years. Sixty diagnosed cases of perinatal HIE were recruited, with twenty children in each of clinical grades 1, 2, and 3 according to the Sarnat clinical staging. All children underwent cycloplegic refraction using atropine 1% eye ointment, visual Acuity (VA) testing by teller acuity cards (TAC), anterior and posterior segment examination, FLASH visual evoked response (VER), strabismus workup, and social maturity assessment using the vineland social maturity scale (VSMS). Results: Sixty children, including 14 preterm and 46 term infants, with a mean age of 26.11 ± 16.06 months were studied. Normal birth weight was observed in 54% of the cases, whereas 42% had low birth weight and 4% had very low birth weight. There was no statistically significant difference between birth weight and the clinical severity of HIE (P = 0.970). A significant relationship between VA and clinical severity (TAC- p < 0.0001) and between VA and social maturity was observed. Optic disc pallor was present in 85% of grade 3 HIE cases. Among the 37 children with strabismus, the convergent type was predominant (86.4%). Refractive error was comparable across all grades of HIE. Conclusion: Visual impairment was significantly related to the clinical severity of HIE and had a negative impact on the social maturity of these children.